Pearl of Wisdom : Human Capital from a World-Class University (1956-2006) : Volume 1 2005 / Corporate Communications & International Relations Office, UiTM - UiTM, Corporate Communications & International Relations Office (Corporate Communications & International Relations Office, UiTM, 2005)
All over the world, universities exist to serve the society that created them. They produce graduates with relevant skills, Jay the foundation for new thoughts and knowledge and provide an avenue for intellectual discourse. Some excel in their role and go on to become world-class universities. UiTM, in celebrating its 50th anniversary, is well and truly on the road to world-class excellence as these pages will testify. We are already a world-class example of social re-engineering and social mobility as witnessed by the breadth and depth of our contributions to the nation. We have successfully upheld the maxim that "education is the basis for human capital development" through the 250,000 alumni of the university. Many of them are now highly successful and some are considered captains of industry. Their contributions to society and the nation are a direct result of our successes. These successes have also spurred us to "reach for the stars" - to amplify our goals and objectives, one of which is to have a student enrollment of 200,000 by the year 2015. Our graduates can be compared to pearls - a precious commodity to be treasured, admired and appreciated by all. In this regard, they are also human capital of distinction, capable of attaining the highest standards of excellence in their personal development and thereby contributing to national development.